INTERJEKSI DALAM NOVEL DONYANE WONG CULIKA KARYA SUPARTA BRATA [Interjection in the novel Donyane Wong Culika by Suparta Brata] - Siti Komariyah (Kantor Bahasa Provinsi Maluku, 2016)
Interjection is a word used to express the feelings of the speaker. This interjection used by the author of the novel to convey the emotion or feeling that not only portrayed through the words or sentences, but also it could be delivered with the other forms of the words that interjection. The study entitled